Global green shift : when Ceres meets Gaia - Mathews, John A. (Anthem other canon economics., 2017)
The greening of industry is described as a global process driven not so much by Western countries concerned with climate change as by China, India and other industrializing countries responding to economic imperatives as they scale up their industrial systems. This is described as economics meeting ecology, or Ceres meeting Gaia.